2021
DOI: 10.36233/0372-9311-92
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of SARS-CoV-2 among residents of the Khabarovsk Krai during the COVID-19 epidemic

Abstract: Introduction. The coronavirus disease (COVID-19) pandemic was announced by WHO in February 2020. In the Khabarovsk Krai, the first three cases of the disease were diagnosed on March 19, 2020, these cases were imported from Argentina (transit through Italy). The epidemic process of COVID-19 in the Khabarovsk Krai is characterized by a slow increase in the incidence. During the period of time when the SARS-CoV-2 seroprevalence study was conducted the incidence rates varied from 35.9 to 39.1 per 100 thousand popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 10 publications
2
3
0
1
Order By: Relevance
“…Moreover, according to the recent study of C Luo et al (2021), SARS-CoV-2 IgG/IgM dynamic is mainly affected by age and disease severity, not sex [16]. However, the present study found a higher seroprevalence in women (37.4%) than in men (17.17-22.89%); these values are similar to those reported from neighboring regions of Russia [25,26]. There are several possible explanations for this result.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Moreover, according to the recent study of C Luo et al (2021), SARS-CoV-2 IgG/IgM dynamic is mainly affected by age and disease severity, not sex [16]. However, the present study found a higher seroprevalence in women (37.4%) than in men (17.17-22.89%); these values are similar to those reported from neighboring regions of Russia [25,26]. There are several possible explanations for this result.…”
Section: Discussionsupporting
confidence: 85%
“…During the pandemic, the assessment of IgM and IgG has been used to diagnose COVID-19, allowing the evaluation of not only the cumulative prevalence of SARS-CoV-2 infection but also the monitoring of seroconversion at the individual and community levels [32,34]. The overall seropositivity estimate in the present study (28.33-28.53%) is similar to that reported from the general population of the Ural Federal District of Russia (24.5-31.3%), which comprises six federal districts: the Tyumen Region, Chelyabinsk Oblast, and Republic of Tatarstan [25,26]. However, our observed seroprevalence is significantly higher than the earlier estimate of 9-10.8% from May to June [24]; this reflects the gradual development of herd immunity and that SARS-CoV-2 continues to spread through the population, resulting in more symptomatic infections and, thus, more seropositive individuals.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Perhaps the publication of this English version of the work will help to fill in information gaps to some extent. Further, it is worth mentioning that a large group of authors have already published 16 articles in Russian publications under the auspices of the head of Rospotrebnadzor, Professor A. Y. Popova [ 17 , 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…или приняты к печати [1,5,6,8,10,13]. Статьи по серопревалентности еще на 13 территориях готовятся к печати.…”
Section: Discussionunclassified